Can Character Traits Be Based on Brute Psychological Facts?. (14th August 2017) - Fileva, Iskra
Abstract: Some of our largely unchosen first‐order reactions, such as disgust, can underwrite morally‐laden character traits. This observation is in tension with the plausible idea that virtues and vices are based on reasons. I propose a way to resolve the tension.